2016
DOI: 10.1111/acel.12485
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent expression ofDNMT1andDNMT3Bin PBMCs from a large European population enrolled in the MARK-AGE study

Abstract: SummaryAging is associated with alterations in the content and patterns of DNA methylation virtually throughout the entire human lifespan. Reasons for these variations are not well understood. However, several lines of evidence suggest that the epigenetic instability in aging may be traced back to the alteration of the expression of DNA methyltransferases. Here, the association of the expression of DNA methyltransferases DNMT1 and DNMT3B with age has been analysed in the context of the MARK‐AGE study, a large‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 38 publications
5
42
1
Order By: Relevance
“…Previous studies have observed global DNA demethylation with aging associated with a lower level of DNMT1 and DNMT3A/B expression. There is a linear decrease in DNMT3B expression with age, while the levels of DNMT1 only gradually decreased up to the age of 64 years (Ciccarone et al ., ). Moreover, Li et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have observed global DNA demethylation with aging associated with a lower level of DNMT1 and DNMT3A/B expression. There is a linear decrease in DNMT3B expression with age, while the levels of DNMT1 only gradually decreased up to the age of 64 years (Ciccarone et al ., ). Moreover, Li et al .…”
Section: Discussionmentioning
confidence: 97%
“…Aging has been associated with gradual DNA methylation changes over the lifespan, marked by global hypomethylation and specific hypermethylation in promoter‐associated CpG islands (Martin, ; Heyn et al ., ). Some studies have linked these changes to alterations in the expression levels of DNMT1 and DNMT3B regardless of nutritional habits, lifestyle, or clinical parameters (Ciccarone et al ., ). In this way, age‐associated ‘epigenetic drift’ can potentially restrict the plasticity of T cells while supporting new phenotypes, such as exhausted or senescent T cells (Fraga et al ., ; Issa, ).…”
Section: Introductionmentioning
confidence: 97%
“…[58][59][60][61] This loss may be attributed to a decline in DNMT1 expression with age. 18 It has been proposed that the loss of CpG methylation at repetitive sequences will heighten the risk of genomic instability due to retrotransposition events, although direct evidence in human aging is lacking. 34,51 In contrast to this general demethylation, DNA methylation arrays have also identified regions of hypermethylation.…”
Section: Dna Methylation In Agingmentioning
confidence: 99%
“…DNMT1 (DNA methyltransferase 1) is the most abundant DNA methyltransferase in mammalian cells and adds methyl groups to hemimethylated CpG di‐nucleotides; its main function is to maintain the methylation during DNA replication. DNMT3A and DNMT3B can methylate hemimethylated and unmethylated CpG, which are critical in establishing methylation states . In humans, 70–80% of CpG cytosines are methylated.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the known age-dependent expression changes of enzymes belonging to the DNA methylation/demethylation machinery [48,49], nutritional and dietary factors can affect Alu DNA methylation status in aging by changing the availability of the methyl donors and altering the activity of the DNMT enzymes [50,51].…”
Section: Discussionmentioning
confidence: 99%